UV and RP-HPLC Estimation of Racecadotril - SRINIVASA RAO, P.; NAPPINNAI, M. (Asian Journal of Chemistry, 2010)
Quantitative method for estimating racecadotril, which is a potent enkephalinase inhibitor, in raw material and from dosage form (capsules), using UV spectroscopy and RP-HPLC, were developed. In the UV method, using ethanol, the λmax was 231 nm and linearity range, limit of detection, limit of quantification, molar extinction coefficient were calculated. In RP-HPLC method, mobilephase used was methanol, acetonitrile, water. Relevant parameters were determined and these methods were used to assay the drug present in raw material and in the dosage form. The results were subjected to statistical analysis and the methods were validated.